Rosa Liebe unterm roten Stern: zur Lage der Lesben und Schwule in Osteuropa - Hauer, Gudrun; Krickler, Kurt; Schmutzer, Dieter (Hamburg: Frühlings Erwachen, 1984)
"Gudrun Hauer, Kurt Krickler, Dieter Schmutzer... et al. Fonds Suzan Daniel (FSD)"